First-Time Magnetic Resonance Imaging Experience: A Descriptive Phenomenological Study with Implications for Nursing Preparation and Communication - Sukanya Juntaree; Arissara Sukwatjanee; Duangduan Rattanamongkolgul (Nursing Reports, 2026)
Background/Objectives: Magnetic resonance imaging (MRI) is often supported by structured safety screening and preparation, yet first-time patients may still experience anxiety, claustrophobic distress, loss of control and non-completion. This study aimed to describe the experiences of adults undergoing MRI for the first time and to identify implications for nursing preparation, communication and diagnostic imaging service design. Methods: A descriptive phenomenological study informed by Husserlian philosophy was conducted in the radiology department of a university hospital in Thailand. Eleven adults who underwent first-time MRI were purposively recruited, including eight who completed and three who did not complete the examination; five participants were hospital personnel. Data were generated through in-depth semi-structured interviews, non-participant observation, audio recording and field notes, and were analysed using Colaizzi’s method. Results: Across the four themes, negotiation of control was identified as a descriptive cross-theme pattern grounded in participants’ accounts rather than as a separate interpretive construct. Participants entered MRI seeking diagnostic clarity, encountered a sensory and spatial environment that weakened control, attempted to regain control through coping and communication, and reflected on the support they would need for any future examination. Four interrelated themes were generated: becoming aware of bodily abnormality and accepting MRI; encountering the MRI environment; managing oneself inside the scanner; and reflecting after passing through the experience. Conclusions: The findings suggest that first-time MRI can be experienced as a nursing-relevant care encounter rather than a neutral technical event. Nursing preparation may need to move beyond routine instructions by addressing sensory realities, anxiety and claustrophobia, coping rehearsal, communication options and post-examination reflection. The effects of these strategies on completion and service outcomes require prospective evaluation.